Chrysin Inhibits Indonesian Serotype Foot-and-Mouth-Disease Virus Replication: Insights from DFT, Molecular Docking and Dynamics Analyses - Susilo, Agus; Cahyati, Miftakhul; Nurjannah, Nurjannah; Pranowo, Dodyk; Hermanto, Feri Eko; Primandasari, Elma Putri (Journal of Tropical Biodiversity and Biotechnology, 2024)
Chrysin, a predominant compound in Propolis, possesses diverse bioactivities, including antiviral properties. However, its antiviral efficacy against the Indonesian Foot-and-Mouth Disease Virus (FMDV) serotype remains unexplored. This study investigates Chrysin's inhibitory potential against FMDV Indonesian serotype by targeting the 3C Protease (3CP), a vital enzyme for viral replication. Multiple sequence alignment was used to reveal unique characteristics of the Indonesian serotype's 3CP compared to global serotypes. Density Functional Theory (DFT) calculations assessed Chrysin's interaction with 3CP based on electronegativity. Molecular docking and molecular dynamics analyses evaluated Chrysin's inhibitory activity against 3CP, using homology modeling for the Indonesian serotype's 3CP structure. Luteolin, a known FMDV 3CP inhibitor with a similar structure to Chrysin, served as a reference. Results showed distinct 3CP sequences in the Indonesian serotype compared to O serotypes and others. Chrysin exhibited potential electron-donor activity with lower HOMO and LUMO values than Luteolin, but they had similar energy gaps, i.e., 4.016 and 4.044 eV, respectively. Molecular docking indicated similar binding affinities, with Chrysin (-6.365 kcal/mol) and Luteolin (-6.864 kcal/mol) bound to active site residues. Molecular dynamics analysis demonstrated stable 3CP-Chrysin and 3CP-Luteolin complexes, with minor differences in Radius of gyration (Rg) and Root-Mean-Square Fluctuation (RMSF) below 1 Å. From the ligand stability point of view, Chrysin had comparable stability with Luteolin. However, Chrysin formed fewer hydrogen bonds and displayed greater free-binding energy than Luteolin during simulation periods. These findings suggest that Chrysin holds promise as an inhibitor of the Indonesian serotype's FMDV 3C Protease.